The mechanics of slender structures. Issue 12 (December 2018) - Reis, Pedro; Brau, Fabian; Damman, Pascal
Modern physics edged mechanics out into the wilds of engineering. But multidisciplinary interest in pattern formation has moved it back into the mainstream, bringing with it interest from other fields — as this summer's Solvay Workshop demonstrated.